Halk kütüphaneleri: Araştırmalar ve Görüşler - Nilay Cevher (Türk Kütüphaneciliği)
This book which is a compilation of previously published (1989-2013) articles, personal opinions, observations and translations of the author underlines the significance of public libraries. While some of the articles belong to the author himself, the rest are joint works. As public libraries are discussed in all its parts, this book is believed to be an easy accessible and well-coordinated source for researchers.